(−)-Complanine, an inflammatory substance of marine fireworm: a synthetic study - Nakamura, Kazuhiko; Tachikawa, Yu; Uemura, Daisuke (Beilstein Journal of Organic Chemistry, 2009)
The synthesis of (−)-complanine, an inflammatory substance of Eurythoe complanata, was accomplished by a “chiral synthon” approach. The absolute configuration of this molecule was determined to be R.
Keywords: chiral synthon; complanine; inflammatory substance; marine fireworm; total synthesis

Poisonous and Venomous Marine Animals of the World - Halstead, B. W. (United States Government Printing Office, 1965)

(untitled) - Nakamura, K.; Tachikawa, Y.; Kitamura, M.; Ohno, O.; Suganuma, M.; Uemura, D. (Org. Biomol. Chem., 2008)

(untitled) - Clark, R. J.; Garson, M. J.; Hooper, J. N. A. (J. Nat. Prod., 2001)

(untitled) - Garrido, L.; Zubía, E.; Ortega, M. J.; Naranjo, S.; Salvá, J. (Tetrahedron, 2001)

(untitled) - Hanessian, S.; Ugolini, A.; Dubé, D.; Glamyan, A. (Can. J. Chem., 1984)

(untitled) - Börjesson, L.; Csöregh, I.; Welch, C. J. (J. Org. Chem., 1995)

(untitled) - Koert, U.; Stein, M.; Wagner, H. (Chem.–Eur. J., 1997)

(untitled) - Langille, N. F.; Jamison, T. F. (Org. Lett., 2006)

(untitled) - Mirzaei, H.; Regnier, F. (Anal. Chem., 2006)

(untitled) - Brady, R. N.; Di Mari, S. J.; Snell, E. E. (J. Biol. Chem., 1969)

(untitled) - Kobayashi, J.-i; Ishibashi, M. (Heterocycles, 1996)